Relationships between corpus callosum and language lateralization in patients with schizophrenia and bipolar disorders. (23rd August 2017) - Tréhout, Maxime; Leroux, Elise; Delcroix, Nicolas; Dollfus, Sonia
Abstract : Objectives: The question of whether there is a continuum or a dichotomy among patients with schizophrenia (SZ) and bipolar disorders (BD) has not been clearly resolved and remains a challenge. Thus, the identification of specific biomarkers of these disorders might be helpful. The present study investigated the volume of the corpus callosum (CC) and functional lateralization for language as potential biomarkers and their relationships in SZ and BD. Methods: The study included 20 patients with SZ, 20 patients with BD and 40 healthy controls (HC). A functional lateralization index (FLI) was computed for each participant within the language comprehension network. For each participant, the volume of the total CC and those of three subregions were extracted. These variables and their anatomo‐functional relationships were investigated. Results: In comparison to HC, SZ patients presented a decreased leftward lateralization for language, whereas this was not found in BD patients. However, as compared to SZ patients and HC, BD patients showed a reduction in CC volume associated with a lower leftward lateralization for language. Conclusions: Our study revealed that SZ patients displayed a reduction of the leftward functional lateralization for language; however, no reduction of CC volume was observed, whereas BD patients presented a decreased volume of the CC associated with a lower leftward asymmetry for language. The results of our study detected distinct anomalies in both SZ and BD that may be considered as specific biomarkers of these disorders related to neurodevelopmental models.